2004
DOI: 10.1111/j.1368-5031.2004.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ezetimibe coadministered with statins: randomised, placebo-controlled, blinded experience in 2382 patients with primary hypercholesterolemia

Abstract: We assessed pooled safety and lipid-regulating efficacy data from four similarly designed trials of ezetimibe coadministered with statins in 2382 patients with primary hypercholesterolemia. Patients were randomised to one of the following double-blind treatments for 12 weeks: placebo; ezetimibe 10 mg; statin; or statin + ezetimibe. Statin doses tested were 10, 20, 40 mg/day (atorvastatin, simvastatin, pravastatin or lovastatin) or 80 mg/day (atorvastatin, simvastatin). Treatment with ezetimibe + statin led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
64
2
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 22 publications
(42 reference statements)
9
64
2
5
Order By: Relevance
“…None of the patients treated with ezetimibe, including those who had previously suffered from statin-related myopathy, developed any treatment-related clinical adverse events or significant changes in hepatic enzymes (e.g., ALT and AST). A US placebo-controlled study of ezetimibe administered alone or in co-administration with statins showed statistically similar rates of adverse events between patients receiving ezetimibe monotherapy and those receiving a placebo and between those receiving statin monotherapy and those receiving co-administration with ezetimibe and any statin therapy 26) . Our findings confirm that ezetimibe has an excellent safety profile when administered alone or in co-administration with any statin.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients treated with ezetimibe, including those who had previously suffered from statin-related myopathy, developed any treatment-related clinical adverse events or significant changes in hepatic enzymes (e.g., ALT and AST). A US placebo-controlled study of ezetimibe administered alone or in co-administration with statins showed statistically similar rates of adverse events between patients receiving ezetimibe monotherapy and those receiving a placebo and between those receiving statin monotherapy and those receiving co-administration with ezetimibe and any statin therapy 26) . Our findings confirm that ezetimibe has an excellent safety profile when administered alone or in co-administration with any statin.…”
Section: Discussionmentioning
confidence: 99%
“…Injury-induced neuroplasticity is also triggered at the onset of brain trauma, including neurogenesis, synaptogenesis, and angiogenesis (Davidson et al, 2004). Whether statins enhance these aspects of neuroplasticity after TBI remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Ezetimibe/statin combination therapy was well-tolerated in 2,382 patients with primary hypercholesterolemia (37). Moreover, the safety and tolerability profiles for the ezetimibe/simvastatin and ezetimibe monotherapy groups were similar in a randomized, double-blind, placebocontrolled trial (38).…”
Section: Safety Of Ezetimibe In Humansmentioning
confidence: 97%